Mussorgsky’s Boris Godunov in Italian: Analyzing the Influence of Michel Delines’ French Version - Stetsenko, Anna (Translation Studies: Theory and Practice, 2024)
This article presents a brief history of Italian rhythmical translations of Modest Mussorgsky's libretto for his opera Boris Godunov, each apparently drawing on Michel Delines’ French version from 1908. The author explores the possibility of studying the opera's reception in Italy in connection with the reception of its translations and conducts a brief comparative analysis of four Italian versions of the opera (two from 1908, one from 1909, and one from 1978) alongside both the original and the French version, using one fragment as an example. The paper also aims to draw attention to the lack of serious studies on opera translations and the translators themselves, emphasizing their role as mediators between different cultures.
Keywords: opera translation; libretto; opera theater; Russian opera; Boris Godunov